Measuring Digital Literacy in Sidoarjo Regency - Ahmad Riyadh Umar Bahlamar,; Abadi, Totok Wahyu (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Digital communication has replaced reading and writing as the primary forms of communication due to the Internet and social media use. In addition, it is critical to comprehend and use digital literacy in a field because of the expanding potential of information and communication technologies. This study aims to evaluate and clarify the level of digital media literacy among residents of the Sidoarjo Regency, describing how digital literacy differs at each level of education and calculating the Sidoarjo Regency's digital literacy index. A sample of 278 respondents for this quantitative descriptive study was selected using the cluster random selection technique. The questionnaires for this survey were distributed using the social media platform, WhatsApp. It consists of eight components of digital literacy, namely the ability to find, select and analyze information; effective communication skills; collaboration capabilities; digital presence capabilities; critical and evaluative thinking skills; creativity ability; the ability to effective practical skills; and cultural, social and ethical abilities. The results of the study show that digital literacy abilities in Sidoarjo Regency based on education vary. Digital literacy skills with junior high school education have an index of 76.35. Those with high school education have a digital literacy index of 79.19. Then those with a Bachelor's degree education have a digital literacy index of 81.17. In general, the digital literacy index for Sidoarjo Regency is 80.83. In digital literacy, the people of Sidoarjo Regency can think critically and evaluatively. The index on this ability is 84.66.